Teacher Collaboration: Implications for New Mathematics Teachers - Laura M. Gellert; Lidia Gonzalez (Arizona State University, 2011)
One increasingly popular way of supporting new teachers is through the use of mentoring. New teachers are often paired with mentors as one of a number of supports meant to aid new teachers as they begin their career. The various types of mentoring range from school based mentors assigned by the school to specialty mentors, such as math coaches. Examples of other types of supports that are thought of as separate from formal mentoring are lesson studies, professional development schools, professional development workshops supported by local universities, teacher networks and sponsored professional development. Given the popularity of policies promoting support for new teachers, we explore specific supports for new teachers in addition to characteristics of these supports by focusing on two new alternatively certified mathematics teachers in New York City. Through observations and both formal and informal interviews that span a year, we gained insight into the various influences on these two teachersâ practice in mathematics and considered how these might inform future practices aimed at supporting new teachers.